Palm kernel cake impact on ruminant physiology, feeding behavior, and muscle physicochemical traits: a meta-analysis - Fhonna, Fenda Alvionita; Jayanegara, Anuraga; Wajizah, Sitti; Asmara Samsudin, Anjas; Samadi, Samadi (F1000 Research, 2025)
<ns5:p>Background The utilization of palm kernel cake (PKC) as a feed ingredient for ruminants has yielded inconsistent findings regarding its effects on animal physiology, feeding behavior, and meat quality. To address these discrepancies, a meta-analysis was conducted by synthesizing data from multiple studies that met specific inclusion criteria. Methods The analysis employed a mixed-model approach to evaluate the impact of PKC inclusion on nitrogen utilization, blood metabolites, feeding behavior, and the physicochemical properties of the <ns5:italic>Longissimus</ns5:italic> muscle in ruminants from 20 relevant articles. These articles originated from Google Scholar, Science Direct, and Springer Link using the keywords “palm kernel cake” and “ruminant.” The analysis was undertaken using the PROC MIXED procedure in SAS® OnDemand for Academics. Results The findings indicate that increasing PKC levels had no significant effects on feeding behavior, nitrogen utilization, blood metabolism, or muscle physicochemical traits. However, a quadratic response (P<0.05) was observed for nitrogen excretion, absorbed nitrogen, and cholesterol levels, suggesting a threshold beyond which PKC inclusion may affect metabolic efficiency. Notably, PKC did not alter meat color, a crucial determinant of consumer preference, implying that its market acceptability remains unchanged. Conclusion These results underscore the viability of PKC as a sustainable protein and fiber source in ruminant diets without compromising animal performance or product quality. Further investigations should explore the optimal inclusion levels of PKC to maximize its benefits while mitigating potential metabolic alterations.</ns5:p>